Digital competencies of deputies of local councils and their role in the formation of local identity of united territorial communities - Viktoria Lola (Aspekti Publìčnogo Upravlìnnâ, 2020)
The publication is devoted to the influence of digital competencies of local council deputies on the formation of the local identity of united territorial communities. It is concluded that in the conditions of digitalization of public administration it is necessary to talk about the formation of virtual social identity of territorial communities as part of their local identity. The question of influence of deputies on processes of their formation is considered. Proposals for the inclusion of digital competencies in the structure of integrated competence of local council deputies have been developed.